1979
DOI: 10.1002/ijc.2910240102
|View full text |Cite
|
Sign up to set email alerts
|

Elevated titer of antibodies to simian sarcoma virus envelope antigen (gp70) and normal response to influenza virus in untreated danish Hodgkin's patients

Abstract: Untreated Danish Hodgkin's disease (HD) patients and paired age- and sex-matched controls were tested for serum antibodies to Epstein-Barr virus (EBV), six strains of influenza virus and Simian sarcoma virus/Simian sarcoma-associated virus [SSV(SSAV)] antigens. HD sera showed significantly elevated titers against EBV and both increased incidence and mean titer of antibodies to the envelope glycoprotein of SSV(SSAV), whereas testing against the influenza viruses revealed no differences between HD and controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Thus, it has recently been found that the envelope glycoproteins of ecotropic and dualtropic (MCF) murine leukemia viruses exhibit qualitative differences in their carbohydrate constituents when grown in the same cell type (M. Kemp Our results emphasize the need for extensive controls in determining the specificity of human antibody recognition of viral protein determinants, especially when sensitive RIP assays are used. In this respect, the recognized influence of neoplasia and chemotherapy on levels of natural heterophil antibodies (29,42) may necessitate some re-evaluation of data suggesting elevated titers of oncoviral antibodies in patients with Hodgkin disease (18). The present data do not exclude the possibility that antibodies in some individuals may result from direct exposure to oncoviruses.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, it has recently been found that the envelope glycoproteins of ecotropic and dualtropic (MCF) murine leukemia viruses exhibit qualitative differences in their carbohydrate constituents when grown in the same cell type (M. Kemp Our results emphasize the need for extensive controls in determining the specificity of human antibody recognition of viral protein determinants, especially when sensitive RIP assays are used. In this respect, the recognized influence of neoplasia and chemotherapy on levels of natural heterophil antibodies (29,42) may necessitate some re-evaluation of data suggesting elevated titers of oncoviral antibodies in patients with Hodgkin disease (18). The present data do not exclude the possibility that antibodies in some individuals may result from direct exposure to oncoviruses.…”
Section: Resultsmentioning
confidence: 63%
“…In the absence of a clearly defined oncovirus of human origin, a number of investigators have approached this problem by investigating human sera for naturally occurring antibodies to oncoviruses of other species. The results obtained have varied from positive to negative or equivocal (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) For preparation of soluble radiolabeled viral 70,000-dalton glycoprotein (gp7O), purified virions were subjected to detergent lysis in a buffer containing 0.05 M NaCI, 0.02 M Tris-HCl (pH 7.4), 0.5% Nonidet P40, 0.5% sodium deoxycholate, and 10% Traysylol protease inhibitor (10,000 kallikrein inactivator units per ml) for 30 min at 370C. After the viral lysates were subjected to centrifugation at 100,000 X g for 60 min in a type 50 rotor, the supernatant fractions containing soluble viral proteins, including radiolabeled gp7O, were collected and stored at -70'C until used.…”
mentioning
confidence: 99%
See 1 more Smart Citation